Mediating role of leadership styles on the relationship between recruitment and selection and employee satisfaction among telecommunication employees - Mohd Sadad, Mahmud; Maged Mustafa, Al-Dubai; Visuanathan, Gopalan (2019)
This paper aims to identify and understand the mediating role of leadership styles on the association that exists between recruitment and selection and employee satisfaction. This study was conducted among 203 employees from four telecommunication companies in Yemen, namely Sabafon, MTN and Yemen mobile. Statistical Package for the Social Sciences tool was used and several statistical methods were involved in the data and statistical analysis including the maximum likelihood estimate. Regression techniques were applied to understand the dimensionality of the variables. The results showed that recruitment and selection has positive relationship on employee satisfaction. In addition, leadership is positively mediating the relationship between recruitment and selection and employee satisfaction. Moreover, the findings showed that appropriate process of recruitment, selection will lead the managers and management to a new dimension with holistic approach in the employee satisfaction arena. Based on the study findings, practical and theoretical implications were discussed.